Determination of nitrofuran metabolites in shrimp muscle by liquid chromatography-photo diode array detection. (February 2017) - Fernando, R.; Munasinghe, D.M.S.; Gunasena, A.R.C.; Abeynayake, P.
Abstract: The use of nitrofurans on any animal in the European Union (EU) and any animal or animal food products intended for export to the EU was banned in 1993 (except furazolidone which was banned in 1995) due to the carcinogenicity of the parent drugs and their metabolites. Thereafter, the screening of food of animal origin for nitrofurans and their metabolites became mandatory for all exports to the EU. This paper describes a High Performance Liquid Chromatography – Diode Array Detection (HPLC-DAD) method to detect tissue bound nitrofuran metabolites, namely 3-amino-2-oxazolidinone (AOZ), 3-amino-5-morpholino-methyl-1, 3-oxazolidinone (AMOZ), semicarbazide (SEM) and 1-aminohydantoin (AHD). The bound residues were hydrolysed and derivatized into the corresponding nitrophenyl derivatives (NPAOZ, NPAMOZ, NPSEM and NPAHD) with 2-nitrobenzaldehyde and analysed by HPLC-UV at 275 nm. The linearity of the photometric detector response to the four derivatized nitrofuran metabolites was verified using matrix-matched calibration standards in the range of 1–20 μg/kg and the average correlation coefficients for NPAOZ, NPAMOZ, NPSEM and NPAHD were 0.9960, 0.9951, 0.9984 and 0.9993, respectively. The decision limit of the method was below the Minimum Required Performance Limit (MRPL) of 1 μg/kg, for all four nitrofuran metabolites, which makes it compatible with the EU requirements. The average recoveries for (fortified samples between 1 and 5 μg/kg) AOZ, AMOZ, SEM and AHD were 107%, 107%, 115% and 114%, respectively. This is the first report of a HPLC-DAD method detecting nitrofuran metabolites below the MRPL according to our understanding. This method has been successfully used with aquaculture and poultry products; however, currently it is validated according to EU guidelines only for shrimp muscle tissue. Highlights: This paper describes an HPLC method to detect tissue bound nitrofuran metabolites. The decision limit of the method was below 1 μg/kg for all four metabolites tested. A financially sustainable and sensitive method to enforce food safety regulations.